Calculating load and intensity using muscle oxygen saturation data - Vasquez-Bonilla, A.; Yáñez-Sepúlveda, R.; Gómez-Carmona, C. D.; Olcina, G.; Olivares-Arancibia, J.; Rojas-Valverde, D. (Sports, 2024)
The study aimed to calculate training intensity and load using muscle oxygen saturation (SmO2) during two differentiated physical tasks. 29 university athletes participated in a 40-m Maximal Shuttle Run Test (MST, 10 × 40-m with 30 s recovery between sprints) and a 3000-m time trial run. Distance and time were used to calculate external load (EL). Internal load indicators were calculated based on percentage of maximum heart rate (%HRMAX) and SmO2 variables: muscle oxygen extraction (Nabla%SmO2) and the cardio-muscle oxygen index (CMOI) was also provided by relating Nabla%SmO2 ÷ %HRMAX, and the training load were calculated as the product of speed (m/min × IL) and the efficiency index [Effindex (m/min ÷ IL)]. A student t test was applied based on Bayesian factor analysis. As expected, EL differed in the 40-m MST (331 ± 22.8) vs. 3000-m trials (222 ± 56.8) [BF10 = 6.25e+6; p = <0.001]. Likewise, IL showed higher values in 40-m MST (39.20 ± 15.44) vs. 3000-m (30.51 ± 8.67) in CMOI: [BF10 = 1.70; p = 0.039]. Training load was greater in 40-m MST (85.77 ± 27.40) vs. 3000-m (15.55 ± 6.77) [(m/min × Nabla%SmO2): BF10 = 12.5; p = 0.003] and 40-m MST (129.27 ± 49.44) vs. 3000-m (70.63 ± 32.98) [(m/min × CMOI): BF10 = 169.6; p = <0.001]. Also, the Effindex was higher in 40-m MST (10.19 ± 4.17) vs. 3000-m (6.06 ± 2.21) [(m/min × Nabla%SmO2): BF10 = 137.03; p = <0.001] and 40-m MST (9.69 ± 4.11) vs. 3000-m (7.55 ± 1.87) [(m/min × CMOI): BF10 = 1.86; p = 0.035]. This study demonstrates calculations of training intensity and load based on SmO2 as an internal load indicator along with speed as an external load indicator during two differentiated exercises.